The Patient and Family Narratives seminars at the University of Saskatchewan connect health professions students with patient experiences - D'Eon, Marcel; Luc, Jelyssa (Canadian Medical Education Journal, 2020)
The Patient and Family Narratives (PFN) seminars make patient perspectives part of the education of students from healthcare professions. These sessions consist of a story shared by a patient, interdisciplinary small group discussions, and a question and answer period. Based on the findings of our evaluation, we will modify the orientation exercise and small group sessions. The simple design of these seminars makes their implementation suitable for other institutions as a way of sharing patient stories in an interprofessional setting. However, the success of a PFN program may depend on a lack of authentic patient contact in the pre-existing curriculum.